Retrospective analysis of gastric cancer management in a real-world setting: a single-institution experience. Issue 2 (April 2020) - Monti, Manlio; Massa, Ilaria; Foca, Flavia; Morgagni, Paolo; Framarini, Massimo; Passardi, Alessandro; Falcini, Fabio; Frassineti, Giovanni Luca
Introduction: In a gastric cancer (GC) setting, phase II and III studies refer to an ideal patient population and only describe a specific category of patients. Older patients or those in poorer clinical condition are generally excluded from clinical trials. We aimed to evaluate therapeutic approaches to GC in a real-world setting at our institute (Istituto Scientifico Romagnolo per lo Studio e la Cura dei Tumori [IRST] IRCCS) over a 10-year period. Methods: A total of 621 consecutive patients with GC diagnosed between January 2000 and December 2009 were considered retrospectively. Among these, 573 with available information on stage of disease were included in the analysis. Demographic and clinical data were collected from paper or electronic medical records. Results: During the study period, 343 (59.8%) patients were diagnosed with GC stage 0 to IIIC (M0): of these, 118 patients had a relapse of disease. A total of 230 patients (40.2%) presented with metastatic disease at diagnosis. Older age was associated with less frequent administration of adjuvant chemotherapy (odds ratio [OR], 0.87; 95% confidence interval [CI], 0.83–0.91); interaction between age and period (OR, 1.02; 95% CI, 1.01–1.03) and stage of disease at diagnosis (OR, 7.95; 95% CI, 3.71–17.1) were positively associated with administration of adjuvant chemotherapy. Older age (OR, 0.87; 95% CI, 0.84–0.90) and presence of comorbidity (OR, 0.46; 95% CI, 0.26–0.83) were associated with less frequent administration of palliative chemotherapy, whereas from 2000–2004 to 2005–2009, patients were more frequently treated with palliative chemotherapy overall (OR, 3.70; 95% CI, 2.01–6.81). Conclusions: Our results confirm that resection is the standard surgical approach to GC, and that chemotherapy is not widely used in adjuvant and metastatic settings. Older age and comorbidities are associated with nontreatment.